Edukasi Tanggap Bencana: Pelatihan Kesiapsiagaan Pramuka Tingkat Penegak dan Pandega: Disaster Response Education Program: Preparedness Training for Rover and Senior Scouts - Rahadian , Maulana Yusuf; Ghozali, Muhammad Thesa; Septiyanna, Rosemaladewi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Simple Emergency Management (SEM) is a straightforward approach to managing emergencies. Non-professionals need to understand the fundamental theories and practices of emergency response. This community service program aimed to offer education and training to scout members of the Penegak and Pandega groups in the Kwartir regions of Gunungkidul, Bantul, Sleman, Kulonprogo, and DIY City. The training program's methodology incorporated a blend of mini-lectures, small group discussions, and hands-on practice. A pre-test was administered before the training, followed by a post-test afterward to evaluate its effectiveness. Statistical analysis of the pre-test and post-test scores of the respondents (n = 25) revealed a notable improvement, with average scores increasing from 57.20 to 85.00. This increase was statistically significant, as evidenced by a p-value of 0.000, according to the Wilcoxon test. These results indicate a significant enhancement in the participants' knowledge following the SEM emergency training.